ECUADORIAN EDUCATION AND ITS RELATIONSHIP IN ECONOMIC DEVELOPMENT FOCUSED ON POVERTY AND INEQUALITY - Andrade Palacios, Julio Cesar Andrade Palacios; Andrade Palacios, Esteban Wladimir; Chandi Yépez, Alonso Javier (Tierra Infinita, 2023)
In recent years, due to the incorrect distribution of resources that arose from political decisions made around Ecuador, an incongruent decrease in the relationship between economic development and education has been observed based on the student context and available resources. The purpose of this study is to analyze the relationship between education and development focusing on the factors of poverty and inequality. Taking into consideration variables such as economic growth and public spending on citizens at the national level. This research is of a mixed longitudinal nature, since it was analyzed from a correlational, descriptive, statistical, documentary and observational point of view. Similarly, a database was created from INEC and the World Bank for retrospective analysis with a quantitative approach using Pearson’s coefficient. In conclusion, it was possible to prove that there is a relationship between education and Ecuadorian economic development. However, the statistics showed that there is both a medium and a low relationship. This is due to the fact that education is not only the only factor involved in improving well-being, but there are also other more influential factors.